Enterprise Governance of Information Technology Achieving Alignment and Value, Featuring COBIT 5 - De Haes, Steven (Springer, 2015)
Featuring numerous case examples from companies around the world, this second edition integrates theoretical advances and empirical data with practical applications, including in-depth discussion on the COBIT 5 framework which can be used to build, measure and audit enterprise governance of IT approaches. At the forefront of the field, the authors of this volume draw from years of research and advising corporate clients to present a comprehensive resource on enterprise governance of IT (EGIT).